Stress and coping styles: the experience of nursing staff working at two public hospitals in Klang Valley, Malaysia - Wan Salwina WI,; Raynuha M,; Ainsah O,; Idayu BI,; Aniza I, (Penerbit UKM, 2009)
Although stress among nursing staff is common, adopting effective coping styles helps in minimizing the problem. The objectives of this study were to compare stress level among nursing staff working in the above disciplines, to identify common coping style used and to determine the relationship between stress and coping styles. This cross-sectional study involved 106 nursing staff who were universally sampled from psychiatric wards and emergency departments in two public hospitals in the Klang Valley. Self-rated questionnaires i.e. Stress Arousal Checklist (SACL) and Coping inventory for Stressful Situations (CISS) were used to assess stress levels and coping styles respectively. There was insignificant difference in terms of stress level between the two nursing staffs. Stress dimension of SACL between the psychiatry (6.53 + 3.18, p=0.372) and emergency (6.02 + 2.67, p=0.372) nursing staffs were insignificant. Arousal dimension of SACL was also insignificant between psychiatry (8.60 + 1.70, p=0.372) and emergency (9.19 + 1.61, p=0.07) nursing staff. Task coping was the most commonly used coping styles among the psychiatry (55.36 + 9.85) and emergency (57.73 + 9.87) nursing staff in this study. Stress dimension of SACL showed weak significant relationship with task coping (r=-0.313, p=0.001) and emotion coping (r=0.292, p=0.001). Arousal dimension of SACL was also found to have weak significant relationship with task coping (r=0.271, p=0.003) and emotion coping (r=-0.251, p=0.005). While nursing was found to be a stressful profession, a significant relationship between stress and coping styles allows intervention to enable better adaptation to the stressful working environment